2019
DOI: 10.5194/acp-2019-589
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How emissions uncertainty influences the distribution and radiative impacts of smoke from fires in North America

Abstract: <p><strong>Abstract.</strong> Fires and the aerosols that they emit impact air quality, health, and climate, but the abundance and properties of carbonaceous aerosol (both black carbon and organic carbon) from biomass burning (BB) remain uncertain and poorly constrained. We aim to quantify the uncertainties associated with fire emissions and their air quality and radiative impacts from underlying dry matter consumed and emissions factors. To explore this, we compare mo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 57 publications
1
35
0
Order By: Relevance
“…Several studies using GFED emissions show that they were able to capture mean surface PM 2.5 observed at IMPROVE sites; however, they emit all fire emissions within the boundary layer (Carter et al, 2020; O'Dell et al, 2019; Spracklen et al, 2007). Our GFED_SFC simulation with fire emissions emitted in surface air also captures the observed surface PM 2.5 levels but still substantially underestimates satellite‐derived AOD and aerosol extinction profiles (blue lines in Figures 3a–3d and S10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies using GFED emissions show that they were able to capture mean surface PM 2.5 observed at IMPROVE sites; however, they emit all fire emissions within the boundary layer (Carter et al, 2020; O'Dell et al, 2019; Spracklen et al, 2007). Our GFED_SFC simulation with fire emissions emitted in surface air also captures the observed surface PM 2.5 levels but still substantially underestimates satellite‐derived AOD and aerosol extinction profiles (blue lines in Figures 3a–3d and S10).…”
Section: Resultsmentioning
confidence: 99%
“…The 2017–2018 extremes provide a rare opportunity to evaluate chemistry‐climate models needed to assess the impacts of wildfires in a warming climate. However, fire emissions used in these models are highly uncertain: Organic carbon emissions in six datasets differ by a factor of 10 over North America (Carter et al, 2020; Pan et al, 2020). Uncertainties also exist in the vertical distribution of fire smoke (Paugam et al, 2016; Rémy et al, 2017; Zhu et al, 2018) and in the representation of fire plume chemistry (Posner et al, 2019; Shrivastava et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Observed OC peaks during summer and fall in the NE, NW, and SW regions and peaks during fall in the SE region. To a large extent, this is driven by wildfire emissions (Carter et al, 2020), as shown in Figure S10. In particular, Southern Appalachian Fires occurred from October to December 2016 in Georgia and North Carolina due to abnormal drought, leading to OC peaks during fall in this region.…”
Section: Resultsmentioning
confidence: 99%
“…However, generating accurate exposure estimates from CTMs requires surmounting several major uncertainties in the pathway between source and receptor. First, large uncertainties in wildfire emissions inventories have been shown to lead to many-fold differences in wildfire-attributed (particulate matter with diameter <2.5 μm) concentrations across the United States (and 20× regional differences in high fire years) when different inventories are used as input to the same CTM ( 15 , 16 ), and integration of satellite observations only slightly improves performance ( 17 ). Second, the detailed conditions surrounding emissions such as the height of emissions injections and very localized meteorology and their transport may not be captured by models and can dramatically impact downstream exposure estimates ( 18 , 19 ).…”
mentioning
confidence: 99%